Commitment to Positive Change: Structural Anti-racism Audit of Nursing Education Programs - Andrea Kennedy; R. Lisa Bourque Bearskin; Kaija Freborg (York University Libraries, 2021)
Amidst many opportunities to create positive change and examine systemic anti-racist decolonial practices (Moorley et al., 2020), we are advocating for concrete action at the root of Nursing education programs by way of a structural anti-racism audit. Based on decolonial and antiracist theory (Garneau et al, 2018; Gaudry & Lorenz, 2018; Kendi, 2019; McGibbon & Etowa, 2009), we propose to engage in systems-level action (McGowan et al, 2020; Mulgan, 2006; van Wijk t al., 2018) and examine institutional structures through an anti-racist framework (Sutton, 2002) based on audit processes for equity, diversity, and inclusion (Chun & Evans, 2019; Olson, 2020; Skrla et al., 2004; Skrla et al., 2009; Zion, et al., 2020). Structures within and influencing curriculum, pedagogy, evaluation will be examined to advance systems-level anti-racist practices and policies (Moorley et al., 2020) with Nursing students, faculty, staff, leadership as a foundation for equitable Nursing education and care (National Collaborating Centre for the Determinants of Health, 2014). This anti-racist approach to Nursing education reform promises to address the pernicious harms of discrimination in the healthcare system, as noted in a recent report on Indigenous-specific racism (Turpel-Lafonde, 2020). We aim to conduct a strengths-based structural anti-racism audit that does not lose sight of disparities (Fogarty et al., 2018). We are currently conducting a literature review and audit framework development and will pilot the structural anti-racism audit in fall 2021. Rather than requesting endorsement of our project, and with respect for diverse approaches, we asked Nursing colleagues to sign this letter to demonstrate shared commitment to critically examine racist challenges and anti-racist opportunities in their Nursing program at a structural level (see this survey: https://forms.gle/tZPN2z1kUoARNPp1A